PHARMACOLOGICALLY ACTIVE SAPONINS FROM THE GENUS ALBIZIA (FABACEAE) - Barbosa, Antony De Paula (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Albizia species (Family – Fabaceae) are endemic in tropical America, Africa and Southeast Asia. Albizia lebbeck, Albizia julibrissin, Albizia gummifera, Albizia chinensis, Albizia adiathifolia and Albizia proceraare some importantly considered species in the traditional medicine. These species are used in folk medicine for the treatment of rheumatism, stomach ache, cough, diarrhea, wounds, anthelmentic and others. Saponins are the main compound present in species of this genus and showed many pharmacological properties as antioxidant, antidiabetic, anthelmentic, antibacterial, hepato protective, anti-inflammatory and cytotoxic. The present investigation reviews the main saponins pharmacologically active of species of the genus Albizia.